Purwarupa Continuous Electronic Self-Enumeration Survey dalam Penyusunan Indikator Pertumbuhan Ekonomi dan Perubahan Harga - Made Sukma Hartania; I Gede Arya Agus Yogantara; I Gusti Ngurah Veryl Tanaka; I Gusti Agung Dwi Purnami (Seminar Nasional Official Statistics, 2022)
The COVID-19 pandemic that has occurred since 2020 has had a real impact in the social and economic fields. The Central Statistics Agency (BPS) which partly collects data has a new data collection strategy. Phenomena of short duration often cannot be captured by surveys conducted over time. Such a phenomenon can only be monitored through incentive data collection at a faster frequency. This study aims to build and test the use of the CELCIUS application in seeing the daily data movements of several respondents. This study uses the self-enumeration method, which has advantages from an economic point of view because it can save survey costs. There are 30 respondents who participated in this survey, which are classified into five groups of business fields. The results of this study indicate that business fields driven by demand from outside the region tend to grow faster than those that only rely on domestic demand. On the other hand, the respondent's perception of price increases is relatively higher than the real price inflation.